Efficacy of the multidisciplinary tumor board conference in gynecologic oncology: A prospective study. Issue 48 (December 2017) - Lee, Banghyun; Kim, Kidong; Choi, Jin Young; Suh, Dong Hoon; No, Jae Hong; Lee, Ho-Young; Eom, Keun-Yong; Kim, Haeryoung; Hwang, Sung Il; Lee, Hak Jong; Kim, Yong Beom
Abstract : Abstract: Evidence has shown that multidisciplinary tumor board conferences (MTBCs) improve patient management for various cancer types. However, few retrospective studies have investigated MTBC efficacy for patients with gynecologic cancers. Here, we prospectively aimed to evaluate how MTBCs influence patient management in gynecologic oncology. This prospective study included 85 consecutive cases that were presented at gynecologic oncology MTBCs in our tertiary university hospital between January 2015 and April 2016. The primary endpoint was treatment plan change rate, which included both major and minor changes. Major changes were defined as exchange, addition, or subtraction of treatment modality. Minor changes included all other, such as intramodality changes or treatment time changes. The secondary endpoints were the change rates of diagnosis, diagnostic work-up, and radiological and pathological findings. The treatment plan change rate, irrespective of changes in diagnostic work-up, was 27.1%, which included 10.6% major and 16.5% minor changes. Among the treatment plan changes, changes in the treatment plan change rate alone were noted in 16.5% of cases, and changes in diagnosis and radiological findings occurred in 7.1% and 3.5% of cases, respectively. Diagnosis and radiological findings, irrespective of changes in diagnostic work-up, were also changed in 9.4% and 10.6% of cases, respectively. However, there were no changes in pathological findings. Moreover, there was a change of diagnostic method for further work-up in 23.5% of cases. The implementation rate of MTBC-determined treatment changes was 91.8%. Gynecologic oncology MTBCs resulted in considerable changes in treatment plans. Diagnosis, diagnostic work-up, and radiological findings were influenced by MTBCs. The data emphasize the importance of adopting a multidisciplinary team approach for gynecologic cancer management.